The calculations of heating of the continuously-casted slugs in the furnaces with pacing beams taking into account cooling of the lower part of slugs - Ju. A. Samojlovich; V. I. Timoshpolskij; I. A. Trusova; D. N. Andrianov; V. A. Matochkin (Литьë и металлургия)
On the basis of the method of finite elements there are solved the problems for calculation of temperature fields of the pacing beams riders and thermal stresses in the continuous cast slugs taking into account cooling of the lower part of slugs at heating in the furnaces of modem construction (with pacing beams).